Dacarbazine-encapsulated solid lipid nanoparticles for skin cancer: physical characterization, stability, in-vivo activity, histopathology, and immunohistochemistry - Bhattacharya, Sankha; Sharma, Satyam (Frontiers in Oncology, 2023)
Background This study examined the use of solid lipid nanoparticles (SLNs) to administer Dacarbazine (DTIC) to skin melanoma cells with minimal adverse effects. Melanoma is a tricky skin cancer to cure, and standard chemotherapy has many negative effects. Encapsulating DTIC in SLNs may allow the drug to target melanoma cells without harming healthy cells. The study developed and tested DTIC-loaded SLNs for skin melanoma treatment. Methods This study encapsulated Dacarbazine (DTIC) in solid lipid nanoparticles (SLNs). SLNs with reversed micelles were produced utilizing specified ratios of the surfactant Kolliphor® P188 and phosphatidylcholine. To track SLN drug localisation, gold nanoparticles were conjugated to the DTIC. Nanoparticle size and form were examined using DLS and TEM. These approaches ensured SLNs had the correct size and shape for drug delivery. Significant findings In the study, various parameters of the developed solid lipid nanoparticles (SLNs) were evaluated, including particle size, zeta potential, polydispersity index (PDI), entrapment efficacy, and cumulative drug permeation. The values for these parameters varied across the different formulations, with particle size ranging from 146 ± 4.71 nm to 715 ± 7.36 nm, zeta potential from -12.45 ± 2.78 mV to -30.78 ± 2.83 mV, PDI from 0.17 ± 0.013 to 0.51 ± 0.023, entrapment efficacy from 37.78 ± 2.78% to 87.45 ± 4.78%, and cumulative drug permeation from 117 ± 4.77 μg/cm2 to 275 ± 5.67 μg/cm2. To determine the optimal anti-cancer formulation, the DTIC-SLNs-8 nanoparticles were mixed with an optimized concentration of Gellan gum (0.01% w/v) and applied to DMBA-induced skin tumors in rats for six weeks, twice daily. Histopathology demonstrated that DTIC-SLNs-8-treated rats had less keratosis, inflammatory responses, and angiogenesis than free DTIC-treated rats. The development of SLNs may be a promising approach for melanoma treatment due to their improved drug retention over the skin. The optimised anti-cancer formulation DTIC-SLNs-8 showed improved efficacy with minimal side effects as compared to free DTIC.